The reality of practicing sports activities modified for people with mild intellectual disabilities from the perspective of the teacher - Shaban, Manal Mohammed Hussain; Al-Jedaani, Amlak Muraddid (Journal of Educational and Psychological Sciences, 2021)
The current study aimed to identify the reality of practicing sports activities modified for people with mild intellectual disabilities from the perspective of the teacher, in light of some variables including "Gender, Academic Qualification and Sector". The sample of the study included of (105) male and female current teachers of intellectually disabled in the governmental and private sectors. They were chosen randomly using the descriptive methodology, and the results concluded that the degree of applying modified sports activities with people with simple intellectual disabilities was moderate, with no statistically significant differences in the domain of (physical sensory environment for sports activities, the degree of availability of human resources qualified to train sports activities, and the role of the teachers of mentally disabled to activate sports activities) are attributed to the gender and the educational qualification variables, with statistically significant differences in the domain of (physical sensory environment for sports activities) attributed to the sector variable and came in favor of the private sector. The researcher recommended the importance of activating the various sporting activities for the intellectually disabled by qualified specialists in order to adopt planned and organized training programs.